Educação na floresta: uma construção participativa de sistemas agroflorestais sucessionais em Japaratuba, Sergipe - Bolfe, Ana Paula Fraga (2004)
The education in the forest comes from to constitute a new relation between the human been with the nature, this one has been suffering transformation throughout the times. One of major examples about this, is the agriculture, which emerged in the moment that the men passed from that what he usually harvested, or from what the nature offered to them, to plant their aliment, modifying drastically the ecosystems. So the agroforestry systems successionals, which means conceivable, groups of herbaceous, arbustives and arborous, that try to reproduce a dynamic sucessional and natural, it s a watershed of agroecology, characterides as a regenerative among men an nature, ruled by the respect, complementarity, diversity, without thinking about the return of Physis but in the coexistence and possessions of life. It s found in the free education, wich ask for the participation, culture, conscience is a fundamental instrument for this way of making agriculture. The agroforestry systems successionals has principles the diversity and the species density, in this order, the local knowledge is essential, and the respect pertaining to the agriculturists and the community. The research develop with agriculturis from Oiteirinhos Farm in the town Japaratuba, in Sergipe, wich the local agriculturists in relation to the agroforestry systems sucessionais and to possibilities a collective appropriating principles that rules in the region. Was verified that the relationship between the agriculturist and nature, the knowledge of the social actors involved in the proposal. After that an elaboration of a geographic data bank proceeded about the use of the land. The implantation of the agroforestry systems successionals, was followed, in the agriculturist and finally the construction of the categories obtained from the voices in interviews and observations of the agriculturists. In the end, this work confirms the importance in dealing with agroforestry systems successionals inherence to a educative process tangent to a environmental sustainability and cultural, so, if it s been constructing territories and territorietalities, and the agriculturist turns info a co-creator for the reality, partner and not dominator, when the inclusion, the participation, the possessions turns info a consequence of a new attitude for been in the world and with the world. To conclude, the perception of these people passed through a modification process, or reconstruction. The collective appropriation of the agroforestry systems successionals went beyond the perception, as a nature, so, showing the methodological proposal of education for agroforestry systems successionals built throughout this long process of implantation.